Effectiveness of HPV Hybrid Capture in Primary Screening of Cervical Lesions On Routine Public Health Care - Veras, Tânia Maria CW; Holanda Junior, Francisco; Lins, Maria Zélia; Gomes, José Túlio; Lima, Francisco de Oliveira; Silva, João Batista; Longatto-Filho, Adhemar; Castekfi, Adauto; Pinheiro, Luiz Gonzaga (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: high risk human papillomavirus (hrHPV) is responsible for almost 100% of the uterine cervical lesions. Objective: to compare hrHPV Hybrid Capture (CH) and conventional Papanicoalou cytology (CC) in the screening performance of uterine cancerous and precancerous lesions. Methods: cross-sectional study assessing sensitivity, specificity and predictive values of both CC and CH to detect cervical lesions. Cervical sampling for CC was initially collected followed by endo and ectocervical sampling for CH, using the Digene kit. Thereafter, patients underwent colposcopy and cervical biopsy if needed. In the presence of an altered colposcopy, histopathology results were the gold-standard. Otherwise, the normal colposcopy was considered. Cervical disease was defined as any intraepithelial lesion (low grade +). Patients with unsatisfactory colposcopy were excluded. Results: a total of 1658 women were included. CC tumed out negative in 1594 (96.6%) women and abnormal cells found in 56 (3.4%): 1.6% (26/56) ASCUS, 0.1% (2/56) AGUS, 1.5% (24/56) CIN I, 0.2% (4/56) CIN II/III. There was no invasive câncer. CH was positive in 19% (315/1658) of the cases. Both CC and CH were negative in 1313 (79.6%) women; 303 (18.4%) were positive in one of the two tests, and 34 (2%) were positive for both. 1602 women with negative CC, 281 (17.5%) showed positive CH. In 22 (1.3%) women, CH was negative and CC positive; however, only two patients showed LSIL. On the other hand, 315 cases with positive CH, 281 (89.2%) had negative CC, with 8.5% (24/281) of women with histologically confirmed lesion. CH sensitivity (71.7%) was significantly higher than CC (30.2%) [p < 0.001], but CC showed higher specificity than CH (97.5% and 82.7% respectively; p < 0.001). Conclusion: the adoption of new screening technologies, such as hrHPV HC, taking advantage of the current knowledge on virai etiology and pathogenesis of cervical câncer, could lead to important reduction in mortality caused by this type of câncer.